The Influence of Allergic Biomarkers in Chronic Rhinosinusitis Patients Who Underwent Functional Endoscopic Sinus Surgery - Lin‐Hsin Tsuei; Rong‐San Jiang (OTO Open)
Abstract Objective This study investigates the roles of allergy, serum IgE, serum eosinophils, and tissue eosinophils in chronic rhinosinusitis (CRS) patients undergoing functional endoscopic sinus surgery (FESS). The study aims to evaluate these biomarkers in predicting disease severity and postoperative outcomes. Study Design A retrospective cohort study. Setting A single academic institution. Methods This retrospective study enrolled patients from 2017 to 2023. Preoperative evaluations included blood tests, sinus computed tomography, nasal endoscopy, questionnaires, olfactory tests, acoustic rhinometry, saccharine transit test, and nasal bacterial culture. The number of eosinophils was counted in the surgical specimens. Postoperative evaluations were performed 3 months after surgery. The severity and outcomes of CRS were compared between allergy‐positive and ‐negative groups, IgE‐positive and ‐negative groups, serum eosinophil‐positive and ‐negative groups, and eosinophilic and noneosinophilic CRS groups. Results Ninety‐six CRS patients who underwent bilateral primary FESS were enrolled. Allergy and serum IgE showed limited predictive value for CRS outcomes. In contrast, serum eosinophils and tissue eosinophils were significantly associated with worse preoperative CRS severity, especially in olfactory dysfunction. Both biomarkers demonstrated greater postoperative improvements, with serum eosinophils showing predictive potential for ECRS (sensitivity 73.5%, specificity 78.7%). Conclusion Our results show that allergy testing and serum IgE levels were not reliable tools for CRS severity or outcomes, while elevated serum and tissue eosinophils were associated with worse preoperative CRS severity, particularly in olfactory dysfunction. FESS provided effective improvements in olfactory outcomes in eosinophilic CRS patients. Serum eosinophils could serve as a reliable noninvasive biomarker for predicting disease severity and surgical outcomes in ECRS patients. Level of Evidence 3.